Half a century of sightings data of southern right whales in Mar del Plata (Buenos Aires, Argentina) - Mandiola, María Agustina; Giardino, Gisela Vanina; Bastida, Julián; Morón, Sergio; Rodriguez, Diego Horacio; Bastida, Ricardo Oscar (Journal of the Marine Biological Association of the United Kingdom)
In South-western Atlantic waters, individuals of the southern right whale (SRW) Eubalaena australis spend part of the year (the austral winter and spring) in northern inshore waters where they breed and then migrate to southern feeding grounds during the summer. Mar del Plata (MDP) is located between two main reproductive areas (Península Valdés-Argentina and Santa Catarina-Brazil). The purpose of the present study is to report the presence of SRWs on their journey off the coast of MDP based on sighting records during the past half century. We carried out whale observations through systematic weekly coastal marine mammal surveys in different points of the MDP area from 1966 to 2016. The first SRW sighting was recorded in 1970; since then, sighting frequency has gradually increased, reaching a peak of 28 sightings (N = 63 whales) in 2016. These are unique long-term sighting records of SRWs in Argentina and the first on their journey off the shores of Buenos Aires province. We expect that these results will help local authorities to regulate tourism and other activities in the area and thereby contribute to the conservation of the species. Fil: Mandiola, María Agustina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Giardino, Gisela Vanina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Bastida, Julián. Instituto Nacional de Investigaciones y Desarrollo Pesquero; Argentina Fil: Morón, Sergio. Fundación Mundo Marino; Argentina Fil: Rodriguez, Diego Horacio. Consejo Nacional de ...